Automatic Maintenance Alert System for Heavy Duty Haulage Machines - Prince Asiamah Addo; Lambert Dwomoh; Charles Ofori (Jurusan Teknik Elektro Universitas Andalas, 2022)
The timely maintenance of haulage machines is important to prevent machine breakdown and reduce productivity down time. An unintended breakdown or machine stop due to inadequate maintenance causes huge financial loss to the company due to delivery delays. Excessive maintenance also increases production cost due to down time and workshop maintenance. Most haulage companies like Mantrac Ghana Limited have a maintenance schedule for their customers. However, most of these customers do not maintain these machines on time, largely due to forgetfulness or sheer disregard for the maintenance schedule. It is thus important to implement an automatic alert system to notify operators of this machinery when it is time for maintenance. This paper seeks to design an automatic alert system using ATmega328 microcontroller, SIM900 GSM module and alarm unit. A sensor connected to the engine of the haulage machine is used to monitor the condition and operational hours of the machine. The microcontroller is programmed using proteus software to receive instructions from the sensor and issue commands to activate both the GSM module and the buzzer simultaneously. The type and time of maintenance to be done is displayed on the LED display. A corresponding message is sent via the GSM module to both Mantrac Ghana Limited and the customer to undertake the type of maintenance. It can be concluded that an automatic alert system would improve strict adherence to maintenance schedule and help reduce machine.